2013
DOI: 10.3389/fonc.2013.00115
|View full text |Cite
|
Sign up to set email alerts
|

TERRA Expression Levels Do Not Correlate with Telomere Length and Radiation Sensitivity in Human Cancer Cell Lines

Abstract: Mammalian telomeres are transcribed into long non-coding telomeric repeat-containing RNA (TERRA) molecules that seem to play a role in the maintenance of telomere stability. In human cells, CpG-island promoters drive TERRA transcription and are regulated by methylation. It was suggested that the amount of TERRA may be related to telomere length. To test this hypothesis we measured telomere length and TERRA levels in single clones isolated from five human cell lines: HeLa (cervical carcinoma), BRC-230 (breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Hence, quantification of TERRA by RT-PCR (Reverse Transcriptase-PCR) targeting subtelomeric parts of the RNA molecules, as initiated by Azzalin et al (3), appears to be more appropriate to assess TERRA expression independently of molecule length (Figures 1D,E). In this view, and fitting with our proposal that telomere transcription decreases upon elongation, close examination of Figure 3 data from Smirnova et al (1) revealed that there might be an inverse correlation between telomere length and the number of TERRA molecules measured by quantitative RT-PCR in various HeLa subclones. However, because the cellular systems used in Smirnova et al (1) are different from the ones described in Arnoult et al (2), we cannot exclude that differences may exist between these two studies regarding telomere length-dependent repression of TERRA.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Hence, quantification of TERRA by RT-PCR (Reverse Transcriptase-PCR) targeting subtelomeric parts of the RNA molecules, as initiated by Azzalin et al (3), appears to be more appropriate to assess TERRA expression independently of molecule length (Figures 1D,E). In this view, and fitting with our proposal that telomere transcription decreases upon elongation, close examination of Figure 3 data from Smirnova et al (1) revealed that there might be an inverse correlation between telomere length and the number of TERRA molecules measured by quantitative RT-PCR in various HeLa subclones. However, because the cellular systems used in Smirnova et al (1) are different from the ones described in Arnoult et al (2), we cannot exclude that differences may exist between these two studies regarding telomere length-dependent repression of TERRA.…”
supporting
confidence: 87%
“…A drawback of alkaline treatment however explaining why this is usually not applied for northern blots is that it releases RNA from the gel (Figures 1B,C), making quantifications rather difficult. Smirnova et al (1) do not appear to have included an alkaline treatment step as, despite high differences in telomere length, notably between HeLa parental cells (7 kb) and cells overexpressing telomerase (50 kb), TERRA profiles were similar (Figure 1 of their article). Most probably, a dot-blot analysis of total RNA would have revealed much higher levels of UUAGGG repeats in HeLa cells overexpressing telomerase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, telomeres were found to be actively transcribed into TERRA, which localize to telomeres, and the presence of these molecules at the telomeres was suggested to cause delayed entry into senescence in yeast cells by promoting recombination-mediated telomere elongation at critically short telomeres [42]. Interestingly, however, a recent study showed no correlation between TL, TERRA levels, and radiosensitivity in several human cancer cell lines [43]. Shelterin proteins, in conjunction with DDR mechanisms, have also been shown to be involved in telomere protection and maintenance [11,17].…”
Section: Telomeresmentioning
confidence: 99%
“…Late-passage normal human fibroblasts with short telomeres are more sensitive to IR than their younger counterparts with longer telomeres [196]. Whether this holds true in telomerase-positive cells is still debatable, as a recent study demonstrated no correlation between TL and radiosensitivity in this setting [43]. It has also been suggested that radiosensitivity is correlated with telomere loss, not mean TL, with no observable IR-induced changes in levels of telomerase expression [197].…”
Section: Telomere Maintenance and The Effects Of Ionizing Radiationmentioning
confidence: 99%